Protecting the poor? Impact of the national health equity fund on utilization of government health services in Cambodia, 2006-2013. Issue 6 (13th November 2019) - Annear, Peter Leslie; Tayu Lee, John; Khim, Keovathanak; Ir, Por; Moscoe, Ellen; Jordanwood, Tapley; Bossert, Thomas; Nachtnebel, Matthias; Lo, Veasnakiry
Abstract : Introduction: Cambodia's health equity fund (HEF) is the country's most significant social security scheme, covering the poorest one-fifth of the national population. During the last two decades, the HEF system was scaled up from an initial two health districts to national coverage of public health facilities. This is the first national study to examine the impact of the HEF on the utilisation of public health facilities. Methods: We first investigated the level of national HEF population coverage and health service use made by HEF eligible members using an administrative HEF operational dataset. Second, through multilevel interrupted time series analysis of routine monthly utilisation statistics during 2006–2013, we evaluated the impact of the HEF on hospital and health centre utilisation. Results: The proportion of HEF beneficiaries using hospital services in a given year (4.6%) appeared to exceed rates in the general population (3.3%). The introduction of the HEF was associated with: a significant level change in the monthly number of consultations at HCs followed by a gradual slope increase in time trend and a significant level change in the monthly number of deliveries. Overall, this was equivalent to a 15.6% net increase in number of consultations and 5.3% in deliveries in the first year. At RHs: a significant level change in the number of RH inpatient cases, followed by a sustained slope increase; a significant slope increase in the number of outpatient consultations and in the overall number of newborn deliveries. Overall, this was equivalent to a 47.9% net increase in inpatient cases, 24.1% in outpatient cases and 31.4% in deliveries in the first year. Conclusion: The implementation of the HEF scheme was associated with increased utilisation of primary and secondary care services by the poor.